Online tools in teaching and learning and the problem of ‘Web 2.0’: a case study of an Information Studies Department, Oman - Al Kindi, Salim Said Ali (Curtin University, 2014)
This study addresses the role of various online tools, collectively known as ‘Web 2.0’ tools, in university education within the Gulf Cooperation Council and investigation the problem of ‘Web 2.0’, using as a case study the ‘Web 2.0’ teaching and learning practices of Information Studies Department (ISD) in Oman. The data was collected using a mixed-method approach consisting of three steps: semi- structured face to face interviews, online survey and two case studies.